2021
DOI: 10.1177/03000605211059893
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cigarette smoking on coronary arteries and pattern and severity of coronary artery disease: a review

Abstract: Objective Smoking is a risk factor for coronary artery disease (CAD) and a known factor influencing the severity and pattern of CAD. We summarized evidence regarding the effect of smoking on the number of occluded coronary arteries and the severity and pattern of CAD. Methods We extracted data from observational studies reporting the pattern and severity of CAD in smokers. The quality of studies was assessed using the Strengthening the Reporting of Observational Studies in Epidemiology checklist, and results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 34 publications
0
24
1
5
Order By: Relevance
“…A recent review found that SMOK status was related to CAD severity and the damaged artery's location in the heart. Nevertheless, there was no significant association between SMOK status and the number of damaged vessels and arterial occlusion location [24]. We also found significant differences between males and females in vessel numbers and the vessels involved (LAD), which was higher in males.…”
Section: Discussioncontrasting
confidence: 56%
“…A recent review found that SMOK status was related to CAD severity and the damaged artery's location in the heart. Nevertheless, there was no significant association between SMOK status and the number of damaged vessels and arterial occlusion location [24]. We also found significant differences between males and females in vessel numbers and the vessels involved (LAD), which was higher in males.…”
Section: Discussioncontrasting
confidence: 56%
“…In ve trials, smoking was associated with the severity of CAD. [31] Generally, it is necessary to preselect patients with severe chest pain when employing MDCT as a noninvasive diagnostic method to evaluate advanced CAD to get accurate results. Therefore, the policy implications for MDCT examinations for CAD in the symptomatic population are signi cant.…”
Section: Discussionmentioning
confidence: 99%
“…Non-enzymatic glycation also produces AGEs from the interaction of aldehyde groups of the reducing sugars that interact with proteins, lipids, and nucleic acids [172] . In addition to diabetes, another risk factor for CVD and myocardial infarction is smoking [173][174][175] . Elevated levels of ApoB-100 and albumin AGEs have been found in the blood of smokers [176] .…”
Section: Mechanism Of Glycation and Effects Of Gldlmentioning
confidence: 99%